Reimagining digital health education: Reflections on the possibilities of the storyboarding method. (October 2019) - Lupton, Deborah; Leahy, Deana
Objectives: To use the design method of storyboarding to challenge pre-service health education teachers to work together to think creatively and differently about digital health, to introduce pre-service teachers to the method as a pedagogical technique for use in their own classrooms, to experiment with our methods as a design sociology research project and to analyse the materials generated by the participants. Design: Storyboarding, a design research method for engagement and research that invites participants to generate a narrative using images and words, was used. Setting: We conducted a 3-hour workshop using storyboarding as part of an Australian university programme for pre-service health education teachers. Method: Following an introduction to the sociology of digital health and the possibilities of design methods, the pre-service teachers were formed into groups. Each group was provided with guidelines for imagining a new digital health device. They worked in their groups to generate a narrative in a storyboard format that described how this device would be used as part of everyday life. The groups then presented their storyboard to the class. The storyboards provided the research materials for analysing the sociotechnical imaginaries concerning digital health they presented. Results: We found that the storyboarding method worked well as an engaging and creative exercise for the participants and to generate insights for us as researchers on the ways in which they conceptualised and imagined the role of digital health technologies. However, despite attempts to educate the pre-service teachers in critical thinking in the lead-up to the workshop that emphasised the sociocultural and political contexts of health behaviours, their storyboards largely presented visions of digital health technologies that relied on individualistic behaviour change. Conclusion: After reflecting on the process, our conclusions provide some ideas for the way forward in using storyboarding as a transformative pedagogical and research tool.